Polyamines: fundamental characters in chemistry and biology - Agostinelli, E. (2009)
Polyamines are small cationic molecules required for cellular proliferation and are detected at higher concentrations in most tumour tissues, compared to normal tissues. Agmatine (AGM), a biogenic amine, is able to arrest proliferation in cell lines by depleting intracellular polyamine levels. It enters mammalian cells via the polyamine transport system. Agmatine is able to induce oxidative stress in mitochondria at low concentrations (10 or 100 microM), while at higher concentrations (e.g. 1-2 mM) it does not affect mitochondrial respiration and is ineffective in inducing any oxidative stress. As this effect is strictly correlated with the mitochondrial permeability transition induction and the triggering of the pro-apoptotic pathway, AGM may be considered as a regulator of this type of cell death. Furthermore, polyamine transport is positively correlated with the rate of cellular proliferation. By increasing the expression of antizyme, a protein that inhibits polyamine biosynthesis and transport, AGM also exhibits a regulatory effect on cell proliferation. Methylglyoxal bis(guanylhydrazone) (MGBG), a competitive inhibitor of S-adenosyl-L: -methionine decarboxylase, displaying anticancer activity, is a structural analogue of the natural polyamine spermidine. MGBG has been extensively studied, preclinically as well as clinically, and its anticancer activity has been attributed to the inhibition of polyamine biosynthesis and also to its effect on mitochondrial function. Numerous findings have suggested that MGBG might be used as a chemotherapeutic agent against cancer.